Mempertimbangkan Gagasan Hermeneutika Farid Esack untuk Membangun Kerukunan Hidup Umat Beragama - Muhtarom Muhtarom (At-Taqaddum, 2015)
There is no religion encourages its adherents to commit violance. However, it is not rare acts of violence committed by religious peoples, even by those with a strong religious base and they do it in the name of their religion. In fact, the idea to undertake dialogue and cooperation among believers have often done. However, the passion and intensity of dialogue is still a lot that is done on the basis of sociological and political interests or the like. It has not been coupled with changes in dogma and the more fundamental religious thought, so the dialogue, cooperation and harmony that is generated is only an artificial unity, not a genuine unity. In this context, the “harmony” hermeneutics of Farid Esack uphold pluralism and religious inclusivism is worth considered for developed in Indonesia given one of the causes of tension and violence that the nuances of religion is accentuating the views and attitudes of religious exclusivism.